Ethnic stereotypes in painting through the prism of philosophical reflection - Kurbacheva, Olga V. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The socio-philosophical interpretation of ethnocultural stereotypes in the context of artistic creations is the focus of this article. The study’s applicability is determined by two factors: a new method for comprehending the subject matter, and the rising degree of articulate attention being paid to ethnic issues in general. Through the lens of painting, the author aims to elucidate the historical and cultural patterns and characteristics of how ethnic problems are reflected in the public consciousness. The author demonstrates through the use of artistic creations that painting can serve as a tool for conceptual rethinking and reflection of ethnic issues in society, in addition to serving as a conduit for the most significant sociocultural events. The article focuses on works in which ethnic identity and stereotyping are purposefully reduced, as well as the characteristics of conceptual interpretation and visualisation of ethnocultural identity and ethnic stereotypes.
Keywords: ethnos; ethnic painting; art; orientalism; ethnic identity; ethnic conflict; racism